Redox/pH-responsive hollow manganese dioxide nanoparticles for thyroid cancer treatment - Liu, Jinren; Guo, Changzhi; Li, Chunxiang; Jia, Qiushi; Xie, Zhengrong; Wang, Ziyue; Tian, Hongda; Li, Zhongyuan; Hao, Liguo (Frontiers in Chemistry, 2023)
The nano drug delivery system MnO2/CDDP@PDA-Cy5.5 was synthesized in this study to increase the efficacy of Cisplatin (CDDP) on thyroid cancer and alleviate the damage to normal tissue, with the aim of enhancing the anti-cancer efficacy, increasing the drug load, optimizing the control of drug release, and alleviating the systemic toxicity arising from drug off-target. On that basis, high efficacy and low toxicity win-win can be obtained. In this study, hollow manganese dioxide nanoparticles (MnO2 NPs) were prepared based on the template method. CDDP was loaded into the hollow cavity and then modified with polydopamine (PDA) and Cy5.5, with the aim of obtaining the nano-drug loading system MnO2/CDDP@PDA-Cy5.5 NPs. The NPs precisely delivered drugs by intelligently responding to the tumor microenvironment (TME). As indicated by the release curves, the NPs release CDDP rapidly by inducing the decomposition of PDA and MnO2 under acidic or redox conditions, and Magnetic resonance imaging (MRI) contrast agent Mn2+ was generated. The results of the in vivo MRI studies suggested that T1 contrast at the tumor site was notably enhanced under the Enhanced permeability and retention (EPR) effect. After the intravenous administration, the effective tumor accumulation exhibited by the NPs was confirmed by magnetic resonance imaging as a function of time. Compared with free CDDP, the in vivo therapeutic effect was remarkably increased. As indicated by the above-described results, MnO2/CDDP@PDA-Cy5.5 NPs is a drug delivery system exhibiting diagnostic and therapeutic functions.